Answer:a) x =−1
B) x=1/2y+12
C) m=13
D) x=2
Step-by-step explanation:a) Let's solve your equation step-by-step.
5(3x+7)=20−2(x+1)
Step 1: Simplify both sides of the equation.
5(3x+7)=20−2(x+1)
(5)(3x)+(5)(7)=20+(−2)(x)+(−2)(1)(Distribute)
15x+35=20+−2x+−2
15x+35=(−2x)+(20+−2)(Combine Like Terms)
15x+35=−2x+18
15x+35=−2x+18
Step 2: Add 2x to both sides.
15x+35+2x=−2x+18+2x
17x+35=18
Step 3: Subtract 35 from both sides.
17x+35−35=18−35
17x=−17
Step 4: Divide both sides by 17.
17x/17=−17/17
x=−1
B) Let's solve for x.
2x−y=24
Step 1: Add y to both sides.
2x−y+y=24+y
2x=y+24
Step 2: Divide both sides by 2.
2x/2=y+24/2
x=1/2y+12
C) Let's solve your equation step-by-step.
m(3−4m)=7+4(8−m2)
Step 1: Simplify both sides of the equation.
−4m2+3m=−4m2+39
Step 2: Add 4m^2 to both sides.
−4m2+3m+4m2=−4m2+39+4m2
3m=39
Step 3: Divide both sides by 3.
3m/3=39/3
m=13
D) Let's solve your equation step-by-step.
5x(x+3)=x(5x−3)+36
Step 1: Simplify both sides of the equation.
5x2+15x=5x2−3x+36
Step 2: Subtract 5x^2 from both sides.
5x2+15x−5x2=5x2−3x+36−5x2
15x=−3x+36
Step 3: Add 3x to both sides.
15x+3x=−3x+36+3x
18x=36
Step 4: Divide both sides by 18.
18x/18=36/18
x=2